PERTUMBUHAN ANGGREK Vanda helvola PADA MEDIA YANG DIPERKAYA JUS TOMAT - Muharyati, Yully; Defiani, Made Ria; Astiti, Ni Putu Adriani (Metamorfosa: Journal of Biological Sciences; Vol 2 No 2 (2015)DO - 10.24843/metamorfosa.2015.v02.i02.p03, 2015)
Vanda is one of the most cultivated orchid species.  In nature, Vanda is endangered because it was exploited in large quantities. Orchid genetic viability can be maintained by embryo culture. The study aimed to investigate the growth of Vanda helvola seeds during 12 weeks after cultured. Media Murashige and Skoog (MS) added with tomato juice 100 g/L was used as culture medium. The results showed that embryo could grow on MS medium on stadium 6 th . Protocorm started to form at 9 weeks after cultured. At 12 weeks, percentage of protocorm formed reach almost 24.1%. Tomato juice improved the growth of protocorm of  V.helvola. Key word s : Medium, protocorm, Vanda helvola
Keywords: Medium, protocorm, Vanda helvola